2007
DOI: 10.1097/01.inf.0000247139.89191.91
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dientamoeba Fragilis Infection With Paromomycin

Abstract: Treatment with paromomycin (25-35 mg/kg/d for 7 days) was evaluated prospectively in 15 children with Dientamoeba fragilis infection after 1-month follow-up. At the end of the study, parasitologic effectiveness and clinical improvement were observed in 12/15 (80%) and 13/15 (87%) patients, respectively. Paromomycin appears to be an effective drug for treatment of D. fragilis infection in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
3
19
2
4
Order By: Relevance
“…Therefore, this study is not directly comparable to the current study. To our knowledge, no other studies report on the effect of eradication of D. fragilis in IBS patients, but clinical improvement of gastrointestinal symptoms other than IBS linked to eradication of D. fragilis have been described 24,31,44,45,47,[53][54][55][56][57][58][59][60] suggesting that at least in some individuals D. fragilis is pathogenic. Only two epidemiologic studies deal with the association between D. fragilis and IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study is not directly comparable to the current study. To our knowledge, no other studies report on the effect of eradication of D. fragilis in IBS patients, but clinical improvement of gastrointestinal symptoms other than IBS linked to eradication of D. fragilis have been described 24,31,44,45,47,[53][54][55][56][57][58][59][60] suggesting that at least in some individuals D. fragilis is pathogenic. Only two epidemiologic studies deal with the association between D. fragilis and IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Various antimicrobial therapies have resulted in the successful clearance of D. fragilis and total resolution of gastrointestinal symptoms in infected patients (152,387,445). Paromomycin, secnidazole, iodoquinol, tetracycline, ornidazole, and metronidazole have been used successfully to treat D. fragilis infections (22,152,305,445).…”
Section: Dientamoeba Fragilismentioning
confidence: 99%
“…4,11,12 Numerous studies have shown antimicrobial therapy targeting and eliminating D. fragilis will result in marked clinical improvement for patients suffering from dientamoebiasis. 3,12,13 All patients from both families presented with a repeated D. fragilis infection over prolonged periods of time. Bacterial etiological agents were excluded by routine testing.…”
Section: Discussionmentioning
confidence: 99%